Edukasi Kepada Masyarakat Umum untuk Meningkatkan Pengetahuan Pemilihan Obat dalam Swamedikasi Batuk dan Flu - Rita Septiana; Riski Ishariyanto; Mega Tri Rahmadin; Winanti Winanti; Rudi Wenda; Feby Valerie Novia Ramadhani; Sindi Wahyu Yuliana; Andini Dwi Yulianti (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Cough and flu are common health problems experienced by the public, with high prevalence across various age groups. The widespread practice of self-medication in the community highlighted the need for proper education regarding the rational and appropriate selection of medications. This educational activity was conducted at two strategic locations: the Car Free Day (CFD) in Solo and Taman Jaya Wijaya in Mojosongo. The method involved direct socialization, distribution of educational leaflets, and interactive question-and-answer sessions. The education focused on the differences between dry and productive coughs, appropriate medication choices, flu medicine content, and the use of natural remedies such as herbal treatments. A total of 41 participants from diverse backgrounds joined the activity enthusiastically. The results showed an increase in public understanding of cough classifications, medicine components, and the importance of reading drug labels before purchase. The sessions also emphasized the need to match medications with symptoms and advised consulting healthcare professionals if symptoms did not improve within three days. Positive responses from participants indicated that direct education effectively raised awareness and encouraged more rational and safe self-medication practices.